2002
DOI: 10.4049/jimmunol.168.7.3484
|View full text |Cite
|
Sign up to set email alerts
|

Tumor-Specific CTL Kill Murine Renal Cancer Cells Using Both Perforin and Fas Ligand-Mediated Lysis In Vitro, But Cause Tumor Regression In Vivo in the Absence of Perforin

Abstract: Kidney cancer is a devastating disease; however, biological therapies have achieved some limited success. The murine renal cancer Renca has been used as a model for developing new preclinical approaches to the treatment of renal cell carcinoma. Successful cytokine-based approaches require CD8+ T cells, but the exact mechanisms by which T cells mediate therapeutic benefit have not been completely identified. After successful biological therapy of Renca in BALB/c mice, we generated CTLs in vitro using mixed lymp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
90
0

Year Published

2003
2003
2014
2014

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 119 publications
(95 citation statements)
references
References 42 publications
5
90
0
Order By: Relevance
“…Besides the two main killing pathways, it has been reported that other killing mechanisms, for example the proinflammatory cytokines gIFN and TNFa, have important roles in rejection of pulmonary metastasis of tumor cells. 38 In the study of Poehlein et al, 31 adoptive transfer of effector T cells, which are taken from perforin and gIFN double knockout mice (PKO/GKO), mediated complete tumor regression and cured wild-type animals with established pulmonary metastasis of melanoma cells by a TNF-a mediated killing mechanism. In addition, Smyth et al 39 have reported that, using the Renca carcinoma tumor model, TRAIL expression on NK and NKT cells has effective antimetastatic functions in vivo mediated by a gIFNdependent immune mechanism.…”
Section: Discussionmentioning
confidence: 99%
“…Besides the two main killing pathways, it has been reported that other killing mechanisms, for example the proinflammatory cytokines gIFN and TNFa, have important roles in rejection of pulmonary metastasis of tumor cells. 38 In the study of Poehlein et al, 31 adoptive transfer of effector T cells, which are taken from perforin and gIFN double knockout mice (PKO/GKO), mediated complete tumor regression and cured wild-type animals with established pulmonary metastasis of melanoma cells by a TNF-a mediated killing mechanism. In addition, Smyth et al 39 have reported that, using the Renca carcinoma tumor model, TRAIL expression on NK and NKT cells has effective antimetastatic functions in vivo mediated by a gIFNdependent immune mechanism.…”
Section: Discussionmentioning
confidence: 99%
“…The relative importance of granule exocytosis versus FAS/FASL-mediated lytic activities for tumour control in vivo is controversial. While many studies point to a dominance of the granule exocytosis mechanism, other studies using perforin-knockout mice (Seki et al, 2002) suggest that FAS-dependent apoptosis may constitute a more prominent pathway in vivo. Therefore, it is of concern that most tumour cells, including RCC, are intrinsically resistant to FASmediated killing (Frost et al, 2003).…”
Section: Discussionmentioning
confidence: 99%
“…Subcutaneous injections of NK-stimulating doses of IL-2 or administration of preactivated NK cells (adoptive transfer of LAK cells) showed a 15-30% positive effect in patients with advanced renal cell carcinoma (RCC) or melanoma (MEL) (42). However, both MEL and RCC show a variable susceptibility to apoptosis induced by TNF ligand members (46 -48), and the clearance of murine renal cancer cells in vivo often does not even require the perforin-mediated pathway (49). Thus, antitumor response following IL-2 treatment also involves the NKR-independent pathways of NK (and T) cell cytotoxicity.…”
Section: Nk Cell-based Immunotherapeutic Strategies Against Cancermentioning
confidence: 99%